The AJ519 antibody detects the human TAC/ILR2A protein by western blot - Bosshard, Eliott; Celeny, David; Laszlo, Alexandra; Longepierre, Mélissa; Richard, Maxime; Verdon, Margaux; Bulla, Monica; Sassi, Ali; Guilhen, Cyril (Antibody Reports, 2020)
The AJ519 antibody detects the human TAC protein by western blot.